2018
DOI: 10.3390/ijms19113596
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Heterotrimeric G Protein γ4 Subunit in Rice

Abstract: Heterotrimeric G proteins are the molecule switch that transmits information from external signals to intracellular target proteins in mammals and yeast cells. In higher plants, heterotrimeric G proteins regulate plant architecture. Rice harbors one canonical α subunit gene (RGA1), four extra-large GTP-binding protein genes (XLGs), one canonical β-subunit gene (RGB1), and five γ-subunit genes (tentatively designated RGG1, RGG2, RGG3/GS3/Mi/OsGGC1, RGG4/DEP1/DN1/qPE9-1/OsGGC3, and RGG5/OsGGC2) as components of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…WD40 proteins are involved in various processes, such as growth and development, metabolite biosynthesis, and immune and stress responses [ 13 , 21 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Furthermore, it has been shown in Arabidopsis [ 15 , 46 , 47 ], rice [ 29 , 48 , 49 , 50 ], maize [ 51 , 52 , 53 ], and rapeseed [ 54 , 55 ] that G-proteins are involved in abiotic stresses. In this study, the qRT-PCR analysis showed that the expression of TaGB1-B changed under stress and hormone treatments ( Figure 2 a–i).…”
Section: Discussionmentioning
confidence: 99%
“…WD40 proteins are involved in various processes, such as growth and development, metabolite biosynthesis, and immune and stress responses [ 13 , 21 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Furthermore, it has been shown in Arabidopsis [ 15 , 46 , 47 ], rice [ 29 , 48 , 49 , 50 ], maize [ 51 , 52 , 53 ], and rapeseed [ 54 , 55 ] that G-proteins are involved in abiotic stresses. In this study, the qRT-PCR analysis showed that the expression of TaGB1-B changed under stress and hormone treatments ( Figure 2 a–i).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we immunologically concentrated the Gγ1 and Gγ2 subunits, and then detected them by LC-MS/MS. Gγ3 and Gγ4 in rice have been identified by IP [ 41 , 42 ]. Similar to Gγ1 and Gγ2, Gγ3, and Gγ4 are difficult to detect in trypsin-digested plasma membrane fractions by LC-MS/MS.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent advancements, more emphasis needs to be given to the protein-extraction protocols, especially for proteins that are not abundant. Matsuta et al [30] and Nishiyama et al [31] used the mass spectrometry technique to identify heterotrimeric G γ4 and γ3 subunit proteins that are not abundant. As RGG4 / DEP1 / DN1 / qPE9-1 / OsGGC3 mutants exhibited dwarfism, the tissues that accumulated Gγ4 corresponded to the abnormal tissues observed in RGG4 / DEP1 / DN1 / qPE9-1 / OsGGC3 mutants [30].…”
mentioning
confidence: 99%
“…Matsuta et al [30] and Nishiyama et al [31] used the mass spectrometry technique to identify heterotrimeric G γ4 and γ3 subunit proteins that are not abundant. As RGG4 / DEP1 / DN1 / qPE9-1 / OsGGC3 mutants exhibited dwarfism, the tissues that accumulated Gγ4 corresponded to the abnormal tissues observed in RGG4 / DEP1 / DN1 / qPE9-1 / OsGGC3 mutants [30]. On the other hand, as RGG3/GS3/Mi/OsGGC1 mutants show the characteristic phenotype in flowers and consequently in seeds, the tissues that accumulated Gγ3 corresponded to the abnormal tissues observed in RGG3/GS3/Mi/OsGGC1 mutants [31].…”
mentioning
confidence: 99%
See 1 more Smart Citation